2019
DOI: 10.1371/journal.pone.0213164
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical study on lumbar arteries related to the extrapedicular approach applied during lumbar PVP (PKP)

Abstract: To observe the regional anatomy of the lumbar artery (LA) associated with the extrapedicular approach applied during percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP), we collected 78 samples of abdominal computed tomography angiography imaging data. We measured the nearest distance from the center of the vertebral body puncture point to the LA (distance VBPP-LA, D VBPP-LA ). According to the D VBPP-LA , four zones, Zone I, Zone II, Zone III and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Some studies [ 7 , 8 ] on anatomy and imaging have shown that the extrapedicular and transverse process root-pedicle approach (TPRPA) can be used for PVP, but individual and level selection is required. TPRPA penetrates the pedicle through the root of the transverse process and lateral part of the pedicle, which allows for a greater abduction angle and it is relatively safer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [ 7 , 8 ] on anatomy and imaging have shown that the extrapedicular and transverse process root-pedicle approach (TPRPA) can be used for PVP, but individual and level selection is required. TPRPA penetrates the pedicle through the root of the transverse process and lateral part of the pedicle, which allows for a greater abduction angle and it is relatively safer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal target location for unilateral PVP is one-third anterior and midline of the VB so that bone cement can diffuse to the unpunctured side, which balances the stress on the VB [19,27]. Therefore, the unipedicular approach requires a more aggressive medial-inclination angle, which can lead to complications of facet joint damage, pedicle disruption and spinal-canal intrusion [13,28]; meanwhile, the extrapedicular approach carries the risk of lumbar-artery injury [14][15][16]. In this study, we used the unilateral transforaminal approach to PVP for the treatment of OVCFs.…”
Section: Discussionmentioning
confidence: 99%
“…The operation is performed under local anesthesia so that the patient can be asked about sensations of radiating pain, to avoid the risk of nerve root damage. In the process of puncturing the vertebral surface, the bone needle is placed above the superior notch of the pedicle to avoid injuring segmental vessels [14][15][16], and not beyond the medial margin of the ipsilateral pedicle, to avoid damaging the spinal cord and dura. In our study, we saw no complications of spinal-cord or nerve root injuries, hematomata or bone cement embolism, which further a rmed the safety of this method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8) In this study, a 71 year-old male patient who had a history use in L4 and L5 vertebra, especially in female patients. 12) As forementioned, however, the parapedicular approach can provide a favorable access to the center of the anterior column of vertebra in instrumented vertebra, which has limited access to the transpedicular approach by previously inserted pedicle screws and vertical rod, without significant surgical morbidity. 4) It is known that PMMA cement augmentation though this approach reduces intractable back pain by stabilizing the anterior column, restoring the vertebral height, and reinforcing the pedicle screw construct.…”
Section: Case Presentationmentioning
confidence: 99%